Conceptual Study Of Kashtartav In Ayurveda W.S.R. To Dysmenorrhoea: Literary Review - Jain, Anjali; Meena, Narendra Kumar; Khathuria, Diksha (International Research Journal of Ayurveda & Yoga, 2021)
Dysmenorrhoea is a menstrual disorder that causes chronic, cyclic pain or discomfort in the pelvic region. It is the most common menstrual disorder among adolescent women. It is estimated that more than half of all teenagers suffer from dysmenorrhea, which often affects their daily physical and emotional aspects. It is the leading factor of short-term school absence and has a negative impact on academics and daily activities From an Ayurvedic point of view, Kashtartava is a symptom mentioned in several Yonivyapads, with Vata being the main causative factor of this condition, commonly compared to dysmenorrhea by modern science. All gynecological problems in Ayurvedic classics are described under the heading of Yonivyapad. It is explained in classical text that due to Vegadharana (withholding natural urges), the aggravated Vata moving in reverse directions fills the Yoni resulting in discharge of Artava with difficulty with severe Shoola. The standard treatment for primary dysmenorrhoea consists of nonsteroidal and anti inflammatory drugs, as well as hormonal therapy, which has undesirable side effects. To effectively alleviate dysmenorrhoea, Ayurveda recommends Ritucharya and Dinacharya, diet modification, and Yoga in the form of Asanas, Pranayam, and meditation on a regular basis. If necessary, Uttarbasti, Garbhashaya balyaaushadhi, Anuvasan, or Matrabasti can also be administered. As a matter of fact, this study focuses on the description of Kashtartava based on scattered classical references.